Peningkatan Keinovatifan melalui Penguatan Kepemimpinan Transformasional dan Iklim Organisasi - Atin Sugiarti; Sumardi Sumardi; Rais Hidayat (Universitas Indraprasta PGRI Jakarta, 2023)
Teacher innovativeness is the act of the teacher accepting and creating new ideas to improve and provide benefits to products, processes and services in learning. This research seeks to identify methods and strategies for increasing innovativeness through strengthening transformational leadership and organizational climate. The research was conducted at SMKN throughout Bogor City with a sample of 145 civil servant teacher. Sampling using proportional random sampling technique. This research uses a quantitative method with a path analysis approach and Sitorem. The results of the research are: 1). There is a positive and significant direct effect of transformational leadership on innovativeness with a path coefficient (?y1) = 0,483, 2). There is a positive and significant direct effect of organizational climate on innovativeness with a path coefficient (?y2) = 0,380, 3). The influence of transformational leadership and organizational climate on innovativeness contributes 65,8% and the rest is influenced by other factors with the equation Y = 0,483X1 + 0,380X2 + 0,585, 4). There is a positive and significant direct effect of transformational leadership on organizational climate with a path coefficient (?21) = 0,742, a contribution of 55% and the equation X2 = 0,742X1 + 0,671, 5). There is an indirect effect of transformational leadership on innovativeness through organizational climate of 0,282. Teacher innovativeness can be increased through strengthening transformational leadership and organizational climate by maintaining/developing the application of new services and accepting new ideas and need to improve inspirational motivation, intellectual stimulation, influence of idealism, individual consideration, management system implementation, personal autonomy/freedom, social environmental conditions, the condition of the physical environment, the creation of new ideas, the application of new methods in learning and benefits achieved.